Deactivation of AKT/GSK-3β-mediated Wnt/β-catenin pathway by silencing of KIF26B weakens the malignant behaviors of non-small cell lung cancer. (June 2022) - Chen, Nanzheng; Wu, Qifei; Zhang, Guangjian; Fu, Junke; Geng, Qianqian; Zhang, Yong
Highlights: KIF26B is increased in NSCLC and correlated with poor prognosis. Inhibition of KIF26B displays anticancer effects in NSCLC. KIF26B regulates Wnt/β-catenin pathway by AKT. KIF26B mediates NSCLC progression by AKT-Wnt/β-catenin pathway. Abstract: Kinesin family member 26B (KIF26B) is reported differently expressed in multiple neoplasms and exerts a pivotal role in carcinogenesis. To date, the relationship between KIF26B and non-small cell lung cancer (NSCLC) is unaddressed. This study explored the possible roles and mechanisms of KIF26B in NSCLC. We observed high levels of KIF26B in NSCLC, and demonstrated that high KIF26B levels predicted an overall shorter duration of survival. Functional experiments demonstrated that restraint of KIF26B by gene knockdown exhibited remarkable tumor-suppressive effects in NSCLC in vitro, including repression of cell proliferation, induction of G0/G1 cell cycle arrest, suppression of cell invasion and epithelial-mesenchymal transition, and enhancement of chemotherapeutic sensitivity. The study further revealed that inhibition of KIF26B was able to affect the activation of β-catenin via regulation of the AKT/GSK-3β axis. Moreover, forced expression of β-catenin could reverse KIF26B-silencing-evoked tumor-suppressive effects. Importantly, NSCLC cells with KIF26B silencing exhibited decreased growth potential in nude mice in vivo. Collectively, our data indicate that restraint of KIF26B has a tumor-suppressive role in NSCLC by affecting the AKT/GSK-3β/β-catenin pathway. This work unveils a pivotal role of KIF26B in NSCLC and suggests it as a viable target for anti-NSCLC therapy.